THERAPEUTIC POTENTIAL OF A WATER-BASED POLYHERBAL CREAM CONTAINING TURMERIC, CUCUMBER, AND CORN STARCH IN FIRST-DEGREE BURN HEALING: AN EXPERIMENTAL RAT STUDY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Burn injuries demand rapid and effective treatment to reduce complications and improve tissue repair. We developed a water-based polyherbal cream (turmeric, cucumber, corn starch) to combine anti-inflammatory, antioxidant, hydrating, and exudate-absorbing properties for superficial burn healing. Methodology: (24) rats with range weight (175 g) were into four groups (Each one 6 animals): untreated burn(GA), 1% silver sulfadiazine (GB), polyherbal cream (standard dose)(GC), and polyherbal cream (+50% enriched)(GD). First-degree dorsal burns were created using a 1 cm metal rod heated to 75–80 °C for 10 s. For biochemical assays, serum and tissue samples were collected on days 1, 7, and 14. Healing was evaluated by wound-contraction monitoring, serum FRAP (antioxidant capacity), tissue MDA (TBARS), serum TNF-α and IL-6, and tissue hydroxyproline (collagen marker). For histopathological evaluation, burn-site skin was fixed in formalin, paraffin-embedded, and stained with H&E. the epidermal regeneration, inflammatory degree, fibrosis, and angiogenesis by histology score (0–5).Results: There were no significant between-group differences at day 1 for any parameter. By days 7 and 14, FRAP increased in all treated groups vs untreated, highest in the +50% cream. MDA, TNF-α and IL-6 was lower in all treated groups vs untreated, lowest in the +50% cream. Hydroxyproline rose in all treated groups vs untreated, highest in the +50% cream at day 14. The histopathological changes are included necrosis, inflammatory infiltration, and poor epithelialization in untreated burns. The experimental treated groups reveals low inflammation and improved skin regeneration. By day 14, the +50% cream group had the most advanced epithelial coverage, collagen-rich dermis, and the lowest histology scores, aligning with biochemical indices of enhanced healing.Conclusion: The water-based turmeric–cucumber–corn-starch cream at the +50% concentration promoted first-degree burn healing by improving antioxidant status, reducing inflammatory cytokines, enhancing collagen deposition, and supporting histologically confirmed tissue repair.Aims of the Study: This study represents that the first investigation to evaluate a polyherbal cream (turmeric, cucumber, and corn starch) for the management of first-degree burns. The study tested the therapeutic efficacy and safety of that, tested at both a standard dose and a 50% enriched concentration, in an experimental rat model and compares its healing performance with the conventional 1% silver sulfadiazine ointment, emphasizing its histologically verified impact on inflammation, re-epithelialization, and collagen-rich tissue remodeling, and the adverse local reactions.
Keywords: Burns, Wound healing, Herbal extracts, Anti-inflammatory effects and Phytotherapy.